Prevalence of cerebral palsy comorbidities in China: a systematic review and meta-analysis - Gong, Chao; Liu, Xiaopei; Fang, Liya; Liu, Annan; Lian, Beibei; Qi, Xunzhong; Chen, Shuyue; Li, Huiqing; Zhao, Ming; Guo, Jin; Zhou, Shaobo (Frontiers in Neurology, 2023)
Objectives: This systematic review aimed to comprehensively understand the comorbidity of cerebral palsy (CP) in China.We searched through databases in both Chinese and English until December 2022 to gather cross-sectional studies on the comorbidity of CP in China. After two reviewers independently screened articles, collected the data, and assessed the bias risk, a meta-analysis was conducted using the Stata 17.0 software.A total of 73 articles were included, reporting total comorbidity of 16 articles, with a prevalence of 79.7% (95% CI: 73.8%-85.7%); epilepsy 56 articles, the prevalence was 17.9% (95% CI: 15.4%-20.4%); intellectual disability 48 articles, the prevalence was 58.0% (95% CI: 51.8%-64.3%); speech disorders 32 articles, the prevalence was 48.0% (95% CI: 41.6%-54.4%); hearing disorders 41 articles, the prevalence was 17.2% (95% CI: 13.0%-21.4%); vision disorders 35 articles, the prevalence was 23.1% (95% CI: 16.3%-29.8%). The topographical type of CP was the primary source of heterogeneity in the prevalence of epilepsy; diagnostic criteria for CP, clinical type of CP, GMFCS, publishing time, and topographical type of CP were the primary sources of heterogeneity in the prevalence of intellectual disability; clinical type of CP and topographical type were the primary sources of heterogeneity in the prevalence of speech disorders; and the region was the primary source of heterogeneity in the prevalence of hearing disorders.The prevalence of comorbidities in CP is higher in China. Comorbidities are related to the characteristics, severity, and risk factors of brain insult and have a particular relationship with regional economic development and medical and health level.